Polymorphic landscape of SARS-CoV-2 genomes isolated from Indian population in 2020 demonstrates rapid evolution in ORF3a, ORF8, nucleocapsid phosphoprotein and spike glycoprotein. (December 2021) - Pal, Archana; Dobhal, Shefali; Dey, Kishore Kumar; Sharma, Anish Kumar; Savani, Vivek; Negi, Vishal Singh
Abstract: India, with around 15 million COVID-19 cases, recently became the second worst-hit nation by the SARS-CoV-2 pandemic. In this study, we analyzed the mutation and selection landscape of 516 unique and complete genomes of SARS-CoV-2 isolates from India in a 12-month span (from Jan to Dec 2020) to understand how the virus is evolving in this geographical region. We identified 953 genome-wide loci displaying single nucleotide polymorphism (SNP) and the Principal Component Analysis and mutation plots of the datasets indicate an increase in genetic variance with time. The 42% of the polymorphic sites display substitutions in the third nucleotide position of codons indicating that non-synonymous substitutions are more prevalent. These isolates displayed strong evidence of purifying selection in ORF1ab, spike, nucleocapsid, and membrane glycoprotein. We also find some evidence of localized positive selections ORF1ab, spike glycoprotein, and nucleocapsid. The CDSs for ORF3a, ORF8, nucleocapsid phosphoprotein, and spike glycoprotein were found to evolve at rapid rate. This study will be helpful in understanding the dynamics of rapidly evolving SARS-CoV-2. Graphical Abstract: ga1 Highlights: 953 loci displayed SNP with a total of 1923 alleles. 936 and 17 loci were identified with 2 and 3 alleles, respectively. The majority of SNP loci are at the 3rd nucleotide (C3) of codons. ORF1ab, spike (S), and nucleocapsid (N) displayed positive and negative selection both. ORF3a, ORF8, S, and N are evolving at rapid rate.